THE FUNCTION OF RECOMMENDATION OF A PHARMACISTS IN REDUCE PIMs (POTENTIALLY INAPPROPRIATE MEDICATIONS) OF GERIATRIC PATIENTS AT THE GENERAL HOSPITAL DR. MOEWARDI SURAKARTA - Dewi Isnaini, Ratna; Darmawan, Endang; Yovita Dewi, Fransiska (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
The prevalence of potentially inappropriate medications (PIMs) is quite high in geriatric patients. PIMs can be detected using an explicit prescription indicator (a criterion). Explicit criteria that can be used in the identification of PIMs in geriatric patients include: BEERS Criteria, STOPP Criteria, and START Criteria. This study aims to analyze drugs included in the PIMs category based on BEERS Criteria, STOPP Criteria, and START Criteria. This research is a semi-experimental study (intervening in the form of giving recommendations) with prospective data collection in the geriatric ward of Regional General Hospital Dr. Moewardi Surakarta in the period from October 2019 to January 2020. The results showed that out of 70 patients, there were 47 PIMs, PIMs based on BEERS Criteria for 20 patients (28.6%), PIMs based on STOPP Criteria for 10 patients (14.3%) and PIMs based on START Criteria for 17 patients (24.3%). Bivariate analysis showed that there was a relationship between the incidence of adverse drug events (ADEs), with recommendations that were followed up on PIMs based on BEERS Criteria with an RR value of 25 (95% CI 1,2: 520,7), P = 0.04 and PIMs based on START Criteria with an RR value of 5 (95% CI 1: 35.9), P = 0.04, whereas the results of the bivariate analysis on PIMs based on STOPP Criteria showed that there was no relationship between the incidence of ADEs with the recommendations that were followed up with a RR value of 4 (95% CI 0.13: 119.2), P = 0.50. Based on the results of univariate and bivariate statistical analysis, it can be concluded that there are still many incidents of PIMs based on BEERs Criteria, STOPP Criteria, and START Criteria and pharmacists have an important function to reduce PIMs so that the incidence of ESO due to PIMs can be minimized in the regional general hospital Dr. Moewardi Surakarta.